2009
DOI: 10.2105/ajph.2008.137679
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Smoking-Related Risks and Benefits as Predictors of Adolescent Smoking Initiation

Abstract: Objectives-We used prospective, longitudinal data to directly test whether smoking-related perceptions predict smoking initiation among adolescents.Methods-We administered surveys assessing perceptions of smoking-related risks and benefits to 395 high school students, beginning at the start of their ninth-grade year. We conducted followup assessments every 6 months until the end of 10th grade, obtaining 4 waves of data.Results-Adolescents who held the lowest perceptions of long-term smoking-related risks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
208
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(224 citation statements)
references
References 20 publications
16
208
0
Order By: Relevance
“…The Aligned with other researches [10,11], the results of this study indicated that perception of social interaction play an important role in emergence of high risk behaviors in adolescents, including aggression. Johnson and Tversk believed that the positive perception of social interaction result in risky and highly optimistic assessments, and the negative perception of social interaction result in risky and highly pessimistic assessments [12].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The Aligned with other researches [10,11], the results of this study indicated that perception of social interaction play an important role in emergence of high risk behaviors in adolescents, including aggression. Johnson and Tversk believed that the positive perception of social interaction result in risky and highly optimistic assessments, and the negative perception of social interaction result in risky and highly pessimistic assessments [12].…”
Section: Resultssupporting
confidence: 82%
“…This means that positive thoughts cause the reduction of aggression and negative thoughts of social interactions cause the elevation of aggression among adolescents. Song's research showed that the adolescents with high negative perception of social interaction would become more, willingness toward high risk behaviors [11]. Yazdkhasti in research concluded that there is a negative and significant relationship between perception of social interaction with anger and risk taking level among university students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 418 students, 395 (95% of consenting students) completed a self-administered survey during a classroom period. Further detail on study design have also been described elsewhere (Halpern-Felsher, Biehl, Kropp, & Rubinstein, 2004;Song et al, 2009). …”
Section: Methods Samplementioning
confidence: 99%
“…Indeed, 60% of adolescent smokers believe that they could smoke for a few years and then give up. Young smokers perceive themselves to be at modest risk of tobacco cigarette dependency because they believe they can quit smoking before any harm occurs (7,14). As a consequence, they tend to neglect the risks of developing cancer in the next 20-30 years.…”
Section: Smoking Initiationmentioning
confidence: 99%